Active layer and permafrost microbial community coalescence increases soil activity and diversity in mixed communities compared to permafrost alone - Doherty, Stacey J.; Thurston, Alison K.; Barbato, Robyn A. (Frontiers in Microbiology, 2025)
Permafrost is experiencing rapid degradation due to climate warming. Microbial communities undergo significant compositional and functional shifts as permafrost thaws. Dispersal of microbial communities from the seasonally-thawed active layer soil into newly thawed permafrost may influence community assembly and increase carbon release from soils. We conducted a laboratory soil mixing study to understand how carbon utilization, heterotrophic respiration, and microbial community structure were affected when active layer and permafrost soils were mixed in varying proportions, as what is expected to occur when the terrain thaws. Active layer soil and permafrost collected from two sites in Alaska were mixed in five different ratios and incubated for 100 days at 10°C to reflect current maximum surface soil temperatures at these sites. Respiration rates were highest in the 100% active layer soils, averaging 19.8 μg C-CO2 g–1 dry soil d–1 across both sites, and decreased linearly as the ratio of permafrost increased. Mixing of the two soil layers resulted in utilization of a more diverse group of carbon substrates compared to permafrost alone. Additionally, combining active layer and permafrost soils increased microbial diversity and resulted in communities resembling those from the active layer when soils were mixed in equal ratios. Microbial communities of the experimentally mixed soils did not resemble those collected from the transition zone. Understanding the effects of active layer-permafrost mixing on functional potential and soil organic matter decomposition will improve predictions of carbon-climate feedbacks as permafrost thaws in these regions.